Corruption and Entrepreneurship: How Formal and Informal Institutions Shape Small Firm Behavior in Transition and Mature Market Economies - Tonoyan, Vartuhí; Strohmeyer, Robert; Habib, Mohsin; Perlitz, Manfred (Entrepreneurship Theory and Practice, 2010)
This article explores the determinants of corruption in transition economies of the post–Soviet Union, Central–Eastern Europe, and Western industrialized states. We look in–depth at the East–West gap in corruption, and why entrepreneurs and small business owners become engaged in corrupt deals. Part of the answers lie in the country–specific formal and informal institutional make–up. The likelihood of engaging in corruption is influenced by the lower efficiency of financial and legal institutions and the lack of their enforcements. Also, viewing illegal business activities as a widespread business practice provides the rationale for entrepreneurs to justify their own corrupt activities. Moreover, closed social networks with family, friends, and national bureaucrats reduce the opportunism of the contracting party of the corrupt deal, thus providing breeding grounds for corruption.